Space formation and the power of the mask in the shrines of Badi Al-Zaman, A semiotic reading - Qaid, Ali Ezzi (Journal of Arabic Language Sciences and Literature, 2025)
The maqamat secrets still constitute the aesthetics of the maqama, with the diversity of the maqamat space as a manifestation and function in creating the horizon of the hero and his transformations, Hence comes this study to investigate the maqamat space in the maqamat of Badi’ al-Zaman, not as a narrative component in the structure of the maqama; but rather in its relationship with the hero and its effectiveness in shaping his masks and their power, as a method of camouflage and simile,This study has adopted narrative semiotics as an approach to trace the effectiveness of factors and their transformations within the spatial universe of the maqamat, arriving at knowing the subject of the value of the mask’s authority, focusing on the hero’s relationship with his space to serve his masks.The study concluded that the relationship of the hero of Al-Hamadhani’s Maqamat with the space-time space is one of creation, formation and containment, and a relationship of influence, conflict and confrontation. He was present in the representations of the mask and the containment of the exercise of his authority over the recipient, The maqamat space was formed by the transformations of the hero as an effective space in the creation of illusion and simile, and authority and dominance represented the subject of the value that he sought by resorting to beggary as a means and not an end.